Manifestation Of Multicultural-Based Da'wah Kh. Abdurrahman Wahid In The Era Of Modernization - Muhammad Khadziqun Nuha; Mk Nuha (Universitas Islam Negeri (UIN) Mataram, 2023)
The understanding and knowledge of people who do not know the tradition generally only know the popular tradition, not the philosophical value contained in the tradition, even many people do not recognize the traditions that exist around their own area. The purpose of this research is to: 1.Describe clearly how the acculturation of Sasak culture and Islamic teachings is realized in the Belangon tradition 2. Understand how the people of Kalijaga Baru Village maintain the Belangon tradition. This research is a type of qualitative data, using primary data and secondary data. The data collected in this article was subjected to descriptive qualitative analysis. The results of this study show that: (1) in the Belangon tradition there is a combination of Sasak and Islamic culture, namely the offering of offerings to those present during the belelangon process (2) offerings cannot be taken home by families affected by Â the disaster. (3) The people of Kalijaga Baru Village are always aware that someone has a congenital disease from their ancestors and never leave this tradition.